1484 Accuracy of a Sequential Approach to Identify Young Febrile Infants at Low Risk for Invasive Bacterial Infection. (October 2012) - Mintegi, S; Bressan, S; Gomez, B; Dalt, L Da; Olaciregui, I; Torre, M De La; Palacios, M; Berlese, P; Ruano, A; Benito, J
Abstract : Introduction: Nowadays it is possible to manage as outpatients selected young febrile infants with low risk criteria for serious bacterial infection. A sequential approach, evaluating, firstly, the appearance of the infant, secondly, the urinanalysis, and, finally, the results of the blood biomarkers, including procalcitonin, may identify better low risk febrile infants suitable for outpatient management. Objective: To assess the value of a sequential approach ("step by step") to febrile young infants in order to identify low risk patients suitable for outpatient management and compare it with other ones previously described (Rochester criteria and Lab-score). Methods: A retrospective comparison of three different approaches ("step by step", Lab-score and Rochester criteria) was made in 1123 febrile infants less than 3 months of age attended in seven European Pediatric Emergency Departments. Results: Of the 1123 infants (Invasive Bacterial Infection - IBI-, 48; 4.2%), 488 (43.4%) were classified as low risk criteria for IBI according to the "step by step" approach (vs 693–61.7%- with the Labscore and 458–40.7%- with the Rochester criteria). The prevalence of IBI in the low-risk criteria patients was 0.2% (95% CI 0–0.6%) using the "step by step" approach (vs 0.7%–95% CI 0.1–1.3% with the Labscore and 1.1%–95% CI 0.1–2%- with Rochester). Using the "step by step" approach, 1 patient with IBI was not correctly classified (2.0%, CI95% 0–6.12) vs 5 using the Labscore or Rochester (10.4%, CI95% 1.76–19.04%). Conclusions: A sequential approach to young febrile infants including procalcitonin identifies better patients more suitable for outpatient management.